The Effect of Quality of Work Life on Performance through Motivation and Job Satisfaction at Employee the Department of Cooperatives and SMEs Sragen - Sulistyowati, Yuvita Danik (-)
This study aims to identify and analyze the influence of the quality of work life on performance through motivation and job satisfaction of employees at the Department of Cooperatives and SMEs Sragen. The analysis technique used is using validity and reliability test, linearity test, regression analysis, path analysis, t test, F test, test the coefficient of determination and correlation analysis. The t-test results on the first equation can be concluded that the variable quality of work life and significant positive effect on the motivation. Test results t in the second equation can be concluded that the variable quality of work life and significant positive effect on job satisfaction. The t-test results in the third equation can be concluded that the variable quality of working life, motivation and job satisfaction and significant positive effect on employee performance. Test results F on the third equation together the variable quality of working life, motivation and job satisfaction affects employee performance in the Department of Industry, Cooperatives and SMEs Sragen. The R2 value totaling 0.883 variation can be interpreted Employee Performance in the Industry Cooperative and SMEs Sragen explained by the variable quality of working life, motivation and job satisfaction of 88.3% and the remaining 11.7% is explained by other variables outside the model study as an example of training and supervision. Results of path analysis, it can be concluded that the use of variable motivation and job satisfaction as an intervening variable is not effective, because the direct effect is greater than the indirect effect.Keywords : Quality of Work Life, Motivation, Job Satisfaction, Performance